Soup burns and the roles played by viscosity, solid constituents, epidermal thickness and clothing. (27th December 2019) - Hickman, Hunter N.; Powell, Jared T.; Kerzmann, Tony K.; Cox, Alexandra C.; Buxton, Gavin A.; Ross, Carl
One of the many concerns for parents of young children and caregivers of geriatric patients is the potential for scalds. Skin tissue can be thinner and more susceptible to scalds, and the accidental spilling of hot soups can be a common source of burns. The type of soup, however, may not elicit any such misgivings. Here, we elucidate the effects of reduced skin thickness on the severity of soup burns. In particular, we compare the two most popular types of soups (tomato and chicken noodle) along with hot water, to identify the roles that the viscosity and solid constituents in these different soups may play in the severity of the burn. We find that the more solid constituents in the chicken noodle soup, in particular, prevents the soup from flowing from the skin, which increases the time of exposure to elevated temperatures, and therefore increases the severity of the burn.